PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN SHOPEE XPRESS AMBULU HUB DI JEMBER DENGAN KEPUASAAN KERJA SEBAGAI VARIABEL INTERVENING - Zakiah, Alfinda Hapsari; Hamdun, Edy Kusnadi; Anshory, Muhammad Iqbal (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
This research was created to analyze and find out how work discipline and motivation influence the performance of Shopee Xpress Ambulu Hub employees in Jember with job satisfaction as an intervening variable. The research method used by researchers is a quantitative method with 147 respondents. The data collection method uses a survey method by distributing questionnaires as a research instrument. The data analysis used is the classic Smart Partial Least Square (PLS) 3.0 hypothesis analysis as inferring data. From the analysis, it is shown that work discipline and motivation have a significant effect on job satisfaction. Furthermore, motivation has a simultaneous but not significant effect on employee performance.